PEMBERIAN TIGA BAHAN DASAR PUPUK ORGANIK TERHADAP PERTUMBUHAN, PERKEMBANGAN, DAN KEJADIAN PENYAKIT PADA TANAMAN CABAI RAWIT (Capsicum frutescens L.) VARIETAS AKIYAMA : Pupuk organik; pertumbuhan; perkembangan; intensitas penyakit; produksi - Habibi, Imam; Irawati, Irawati; Mahfud, Cholil; Hardiyanto, Suryo (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2025)
Cayenne pepper (Capsicum frutescens L.) is one of the fruit vegetables that is widely consumed by Indonesian people, because the people’s need for cayenne pepper continues to increase and the price of fertilizer is increasingly expensive, it is necessary to innovate in the method of cultivating cayenne pepper. Efforts that can be made to produce cayenne pepper plants include finding the best varieties of chili plants and applying organic fertilizer, one of which is solid organic fertilizer made from waste coffee grounds, banana peels and egg shells, where organic fertilizer is safer if used long term. Long and can also reduxe the rate of use of chemical/synthetic fertilizers. The UNISKA Integrated Field Laboratory in Rejomulyo Village, Kediri City District, was the site of this study from December 2023 to August 2024. Located at an elevation of 67 meters above sea level, this area has a reasonably flat surface. The temperature is 31.2ºC, and the relative humidity is 62.3%. The land's soil is a sandy regosol, which has a pH of 5.8 and is grayish brown in color. According to the study's findings, using organic fertilizer had a noticeable effect on the therapy. In the threatment of plant height,number of leaves, and number of fruit there was a significant influence, and when observed, the intensity of the antracnose disease attack was 0% and the yellow disease attack in the positive control was 2.25%.